ESCUELA INFANTIL, CIUDAD Y DEMOCRACIA: BUSCANDO EL EJERCICIO DE LA CIUDADANÍA INFANTIL - Canavieira, Fabiana Oliveira (2020)
This article is a dialogue between perspectives that think about the education of children in articulation with the visibility and the guarantee of the right to the urban space of cities. This is a clipping of Canavieira's doctoral thesis (2019) that addresses democratic conceptions and practices in early childhood education. We start from the studies of Sennett (2016 and 2016), Lefebvre (2001), Lopes (2006 and 2018), with the main objective to highlight political-pedagogical conceptions and practices that catalyze the integration of babies and young children in through the institutions of early childhood education and the relationship between public and political space. We defend the possibilities of territorialization of children in the urban space as an exercise of democratic practice and citizenship and the power of early childhood education in this process, problematizing the elements of the process of deterritorialization of the child body in the public space. Therefore, we discuss the idea of educational territory coined in the reality of Paulistana Early Childhood Education. We argue that political- pedagogical intentionality based on democratic principles can guarantee young children the right to the city, and the formation of citizen bodies, minds and subjectivities.